Prediction of flow stress and microstructure evolution mechanism during thermal tensile process of ZK60 alloy - Liu, Fangjia; Yang, Chong; Liao, Zijun; Wu, Hairui (Frontiers in Materials, 2024)
In this work, the hot deformation behavior and microstructure evolution of ZK60 alloy are investigated. Meanwhile, constructive models and hot processing maps of ZK60 alloy during thermal tension are also established. Toward these ends, thermal tensile tests were performed at elevated deformation temperatures (523 K–673 K) and wide-ranging strain rates (0.0005 s−1 to 0.1 s−1). The findings indicated that as the tensile temperature increases and the strain rate decreases, the flow stress exhibited a decrease. To better evaluate the flow behavior of the alloy, Arrhenius model coupled strain effects and particle swarm optimization support vector machine (PSO-SVM) regression model are developed. Both the developed Arrhenius model and PSO-SVM regression model could depict the flow stress of the hot deformation ZK60 alloy. However, the results comparison revealed that the PSO-SVM regression model provides a more accurate prediction of the stress in the studied alloy with the AARE and R of 1.12% and 0.9984, respectively. The microstructure observation revealed that the primary softening mechanism in the alloy is predominantly dynamic recrystallization (DRX). Using the created hot processing map, the stability processing areas for this alloy were concentrated in the range of 573 K–653 K with a strain rate of 0.001 s-1 to 0.08 s-1. The described model is implemented in the finite element software. Then, the wire-drawing process of ZK60 alloy is also simulated.